2014
DOI: 10.1136/bcr-2013-201682
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic dilemma in a case of osteolytic lesions

Abstract: A middle-aged male patient presented with fever, polyarthralgia, polyuria, easy fatigability and weight loss for 1 month. Clinically, there was only significant pallor and a swelling over the right sternoclavicular joint. On investigation, there was anaemia, raised urea, creatinine and pus cells in urine with growth ofEscherichia coli. There were also hypercalcaemia and osteolytic lesions over the ribs, scapula, clavicle and skull along with distorted renal corticomedullary differentiation. Although the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…There are always exceptions in medicine, and this should be taken into account for diagnosis. This is an important reminder that patient’s with a particular presentation may be misdiagnosed or mistreated or at least delayed diagnosis if we are not diligent enough, as previously highlighted by Mandal et al 21…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…There are always exceptions in medicine, and this should be taken into account for diagnosis. This is an important reminder that patient’s with a particular presentation may be misdiagnosed or mistreated or at least delayed diagnosis if we are not diligent enough, as previously highlighted by Mandal et al 21…”
Section: Discussionmentioning
confidence: 78%
“…However, it is rare for NHLs to present with hypercalcaemia and lytic bone lesions like our patient as an initial presentation. Through our literature review, we came across seven such cases reported previosuly 7 8 21–24. These are presented in table 1.…”
Section: Discussionmentioning
confidence: 99%
“…CRAB like initial presentation mimicking active myeloma is uncommonly reported in the literature. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] In this manuscript we describe a middle-aged female subject who presented with clinicoradiological and biochemical features secondary to metastatic breast cancer mimicking CRAB positive myeloma and present a comprehensive review of all such CRAB positive nonmyelomatous malignancies reported in the literature.…”
Section: Crab (Hypercalcemia [C] Renal Dysfunction [R] Anemia [A] Bon...mentioning
confidence: 99%
“…There were twenty-two cases of CRAB positive nonmyelomatous malignancies (M:F = 1:1) the details of which are briefly summarized in Table 1. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] The median age at presentation was 58. G reversal was described in a case reported by Roy et al in a case of primary osseous Burkitt lymphoma.…”
Section: Crab (Hypercalcemia [C] Renal Dysfunction [R] Anemia [A] Bon...mentioning
confidence: 99%
See 1 more Smart Citation